Edukacja zdalna. Adaptacja procesu dydaktycznego do potrzeb osób z niepełnosprawnościami - Migacz, Justyna (Virtualizing the lives of people with disabilities, 2021)
The article presents information on the adaptation of the study process to the needs of selected groups of people with disabilities. The article focuses on adapting remote education. The concept of adaptation of the education process was defined. Suggestions for communication with people with disabilities were presented. Adaptations of remote education divided into groups of people with disabilities were presented. The information presented in the article is based on the literature on the subject as well as the author’s observations and experience. The article contains practical knowledge. Due to the experience of the author, a significant part of the article is devoted to discussing the adaptation of remote education to the needs of people with visual disabilities. The article highlights the differences between distance and conventional education. Differences in the adaptation of the education process of people with disabilities resulting from the use of remote education were indicated.